2019
DOI: 10.3389/fnins.2019.00814
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Spindles and K-Complexes and the Role of the Dorsal Caudal Part of the Anterior Cingulate as the Generator of K-Complexes

Abstract: The large multicomponent K-complex (KC) and the rhythmic spindle are the hallmarks of non-rapid eye movement (NREM)-2 sleep stage. We studied with magnetoencephalography (MEG) the progress of light sleep (NREM-1 and NREM-2) and emergence of KCs and spindles. Seven periods of interest (POI) were analyzed: wakefulness, the two quiet “core” periods of light sleep (periods free from any prominent phasic or oscillatory events) and four periods before and during spindles and KCs. For each POI, eight 2-s (1250 time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 120 publications
1
16
0
Order By: Relevance
“…In a future study, we plan to directly compare ear-EEG channel combinations with EEG measured at several scalp positions to further validate ear-EEG solutions for sleep EEG acquisition. Recently, suggestions have been made for the source of sleep spindle and K-complex generators ( 33 , 34 ) that may facilitate an ideal layout of bipolar channels on the hairless skin to best capture sleep characteristics. In the future, a generator-driven approach may be helpful to place bipolar channels in a way that ideally capture the source of sleep stage characteristics like sleep spindles and K-complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In a future study, we plan to directly compare ear-EEG channel combinations with EEG measured at several scalp positions to further validate ear-EEG solutions for sleep EEG acquisition. Recently, suggestions have been made for the source of sleep spindle and K-complex generators ( 33 , 34 ) that may facilitate an ideal layout of bipolar channels on the hairless skin to best capture sleep characteristics. In the future, a generator-driven approach may be helpful to place bipolar channels in a way that ideally capture the source of sleep stage characteristics like sleep spindles and K-complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed study of the whole brain activity for NREM2 has revealed a systematic change from NREM2c to the periods just before and during spindles and KC1 events ( Ioannides et al, 2017 , 2019 ), supporting specific interpretations of the roles of KC1 and spindles. A KC1 event has a Janus face ( Halász, 2016 ) because it serves simultaneously arousal and sleep promoting roles.…”
Section: Introductionmentioning
confidence: 76%
“…One of the problems was that the hallmarks of individual sleep stages sometimes appear together in the same 30 s period to be scored, thus making a unique and unambiguous definition impossible. We now know, that many of the hallmarks used for sleep staging are characterized by “widespread intracranial activity with unexpected synchrony” when studied from either intracranial recordings ( Frauscher et al, 2015 , 2020 ; Latreille et al, 2020 ) or tomographic estimates of activity extracted with MFT from MEG data ( Ioannides et al, 2017 , 2019 ). One may wonder why so much emphasis is placed on obtaining consistency in sleep staging classification which is determined by highly variable and wild excursions in the signal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations